(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
There are many unique aspects of the treatment of cerebral palsy, in which only the constant long-term continuation of a multidisciplinary comprehensive rehabilitation program brings relief to the patient and improves his quality of life. If the patient can take care of himself, this is a great achievement for society and, of course, for his family. The direct active participation of the patient in this rehabilitation increases the effectiveness of this method. The help of psychologists in this is certainly invaluable. With the joint support of several specialists, it is possible to prepare the patient for an active life and increases the patient’s interest in life